On the physical processes ruling an atmospheric pressure air glow discharge operating in an intermediate current regime - Prevosto, Leandro (2015)
Low-frequency (100 Hz), intermediate-current (50 to 200 mA) glow discharges were experimentally investigated in atmospheric pressure air between blunt copper electrodes. Voltage–current characteristics and images of the discharge for different inter-electrode distances are reported. A cathode-fall voltage close to 360V and a current density at the cathode surface of about 11 A/cm2, both independent of the discharge current, were found. The visible emissive structure of the discharge resembles to that of a typical low-pressure glow, thus suggesting a glow-like electric field distribution in the discharge. A kinetic model for the discharge ionization processes is also presented with the aim of identifying the main physical processes ruling the discharge behavior. The numerical results indicate the presence of a non-equilibrium plasma with rather high gas temperature (above 4000 K) leading to the production of components such as NO, O, and N which are usually absent in low-current glows. Hence, the ionization by electron-impact is replaced by associative ionization, which is independent of the reduced electric field. This leads to a negative current-voltage characteristic curve, in spite of the glow-like features of the discharge. On the other hand, several estimations show that the discharge seems to be stabilized by heat conduction; being thermally stable due to its reduced size. All the quoted results indicate that although this discharge regime might be considered to be close to an arc, it is still a glow discharge as demonstrated by its overall properties, supported also by the presence of thermal non-equilibrium. VC 2015 AIP Publishing LLC. [http://dx.doi.org/10.1063/1.4907661]